Pathogenicity Variation and Population Genetic Structure of Plasmopara viticola in China. Issue 11 (19th August 2016) - Li, Xinlong; Yin, Ling; Ma, Lingjun; Zhang, Yali; An, Yunhe; Lu, Jiang
Abstract: Viticulture in China, like in many other major grape‐growing countries around the world, is severely affected by downy mildew (DM) disease caused by Plasmopara viticola (Pv). However, little has been known about the pathogenicity and genetic structure of the pathogen distributed in China. In this study, 206 single‐sporangiophore Pv strains were isolated from Pv‐infected leaves collected from the most important grape‐growing regions in China. Among them, 29 strains, isolated from a majority of sampled regions and from the hosts with different DM resistance, were tested for their pathogenicity by inoculating into six grape cultivars with different levels of DM resistance. Significant difference in pathogenicity was observed among these strains. Seven pairs of SSR primers selected from previous reports were used for genetic studies of these 206 Pv strains. A total of 64 alleles and 193 genotypes were identified, suggesting that oosporic infection resulted from sexual reproduction made the major contributions to the disease epidemics during the growing season. Analysis of molecular variance (AMOVA) and principal coordinate analysis (PCoA) showed that most of genetic variations were within populations. In addition, low levels of pairwise FST value (ranged from 0.02 to 0.07) and high levels of gene flow were detected between populations. Results from this study suggest that long‐distance dispersals of Pv oospore occur in China.